(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis is devoted to the study of phraseology, a branch of linguistics that deals with the structure, meaning, and use of fixed expressions, idioms, collocations, and phrasal units in a language. Phraseological units are essential elements of any language, as they reflect the culture, traditions, and worldview of its speakers. The paper discusses different types of phraseological units, their classification based on structure and semantics, and their functions in communication. Special emphasis is placed on English and Uzbek phraseological expressions, drawing comparisons between them and analyzing their cultural relevance. The study also highlights the importance of learning phraseology for language learners, as mastering idioms and set expressions greatly improves fluency and understanding of native-level speech. By exploring the richness of phraseological units, this paper aims to show how they contribute to the expressiveness and emotional depth of language.